Cloud computing and services science : 9th International Conference, CLOSER 2019, Heraklion, Crete, Greece, May 2-4, 2019, Revised Selected Papers /: 9th International Conference, CLOSER 2019, Heraklion, Crete, Greece, May 2-4, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available